INTERNATIONAL MOVEMENT OF CAPITAL - DEBT FINANCES: THE CASE OF SIX POST-COMMUNIST ECONOMIES - Raisová, Manuela (Journal of Advanced Studies in Finance, 2011)
Foreign loans represent an attractive source of external financing for countries with relatively low domestic capital base while in developed economies it is considered to be a suitable form of investment for foreign investors in investment portfolio creation. As an additional source of capital it helps less developed countries to finance their economic activities. Empirical literature suggests debt capital inflows have a significant impact on various indicators in the foreign debt capital target economy and its productivity. In the paper we analyze various effects of debt capital inflows on the selected economic indicators in the capital receiving country. Our research includes countries which have undergone the transformation process recently, while they share another common characteristic feature, namely they have been functioning as independent economies for a very short period of time.